Practical guidance to advisors of residents on the fellowship selection process - Richard Alweis; Amr Salama (Greater Baltimore Medical Center, 2021)
Inability to Match into a fellowship is usually not a reflection of some failure on the part of the resident, but rather a problem of supply and demand. Understanding how to advise residents to maximize their success in an environment with limited spots and limited fellowship faculty resources to perform holistic review remains one of the primary objectives of most residency mentors. Residents can alter the odds in their favor by engaging with local faculty and in national society mentorship programs, performing 'enough' research, building their 'brand,' and concentrating on high quality personal statements.